Tensiones jurisdiccionales sobre el fuero que cobija a la mujer en estado de embarazo (2019)
In the Colombian legal system, pregnant women workers, instead of special protection in the employment relationship, can not be terminated unilaterally due to pregnancy during the time it lasted and maternity leave. The mandate of the constitution is based on the protection of the head. However, judges are interpreters of the law who are engaged in developing all the characteristics, conditions, conditions and elements that cover the figure through the jurisprudence they issue. The present investigation refers to the different degrees of protection that women have been granted in the state of gravity by the jurisprudential development and thetensions and disagreements that up to now have been presented in the Constitutional Court and the Supreme Court of Justice. to the figure